2010
DOI: 10.1111/j.1556-4029.2010.01501.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitreous Humor: Biochemical Constituents in Estimation of Postmortem Interval*,†

Abstract: Analysis of biochemical constituents of the vitreous humor can be useful in determining the postmortem interval as there is proportionate postmortem rise of potassium and fall in sodium concentration. We studied 120 autopsy cases to determine the utility of potassium, sodium, calcium, and chloride levels, and sodium/potassium ratio in estimating the postmortem interval. There was a linear relationship between vitreous potassium concentration and postmortem interval, whereas an inverse relationship between vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
61
0
19

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(92 citation statements)
references
References 22 publications
12
61
0
19
Order By: Relevance
“…However, it was also found that the correlation between vitreous electrolytes and time since death was not statistically significant [20]. It has been concluded that the sodium, calcium, and chloride levels have no role in estimating PMI [23].…”
Section: Applications Electrolytesmentioning
confidence: 94%
See 2 more Smart Citations
“…However, it was also found that the correlation between vitreous electrolytes and time since death was not statistically significant [20]. It has been concluded that the sodium, calcium, and chloride levels have no role in estimating PMI [23].…”
Section: Applications Electrolytesmentioning
confidence: 94%
“…Over the years, many scientists have confirmed the existence of this relationship and created different formulas to estimate the time of death with varying accuracy [33][34][35]. Many of the statistical models and equations derived to estimate time since death are based on the assumption that the postmortem increase in vitreous potassium is fairly linear with time and changes at a constant rate [23]. There are studies in the literature reporting a not entirely linear relationship between vitreous potassium and PMI [30].…”
Section: Applications Electrolytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Bu değişimlerin cesette neden olduğu değişiklikler esas alınarak PMİ tahmini yapılmaktadır. PMİ tahmininde kullanılan yöntemlerin başlıcaları; ölü lekeleri (1)(2)(3)(4)(5), ölü katılığı (6,7), ölü soğu-ması (2,(8)(9)(10), vücut sıvılarının postmortem biyokimyasal incelemeleri (2,3,6,7,(11)(12)(13)(14)(15)(16) mide boşalması (1,2,7), elektrofizyolojik çalışmalar (17,18), flow-sitometrik ça-lışmalar (19,20), mikrobiyolojik çalışmalar (21-23) ve entomolojik çalışmalardır (24-34). Bunun dışında ülke-mizde yapılan, iskelet kas dokusundaki postmortem element seviyesi tespiti (35), beyaz kan hücrelerindeki deği-şim (36) ve böbrek üstü bezinin morfometrik değişiklik-lerinin tespiti (37) ile de postmortem interval konusunda yapılmış çalışmalar bulunmaktadır.…”
Section: Introductionunclassified
“…Günümüzde ölüm zamanı ile ilgili olarak pek çok araştırma yapılmış olmakla birlikte, + uygulamada postmortem değişimler ve vitröz sıvı K değeri dışında çok fazla yöntem kullanılmamaktadır (1)(2)(3)(4)(5).…”
Section: Introductionunclassified